2015
DOI: 10.3892/mmr.2015.4028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wnt/β-catenin signaling on bisphenol A exposure in male mouse reproductive cells

Abstract: Bisphenol A (BPA) is a chemical used in numerous consumer products that is able to interfere with the mammalian endocrine system. The aim of the present study was to investigate the effects of BPA on male mouse reproductive cells following prenatal to postnatal exposure. In addition, the influence of BPA was detected on the expression levels of β‑catenin and dickkopf WNT signaling pathway inhibitor 1 (DKK‑1) during the differentiation of spermatogenic cells in the mouse testes. β‑catenin and DKK‑1 are two impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
6
1
1
Order By: Relevance
“…Herein our results clearly indicated that BPA significantly increased the protein expression of tenascin-C as well as β-catenin. An interaction between β-catenin and tenascin-C 66,67 is known to occur and may also trigger podocytopathy as described in other cell types 68,69 .…”
Section: Discussionmentioning
confidence: 99%
“…Herein our results clearly indicated that BPA significantly increased the protein expression of tenascin-C as well as β-catenin. An interaction between β-catenin and tenascin-C 66,67 is known to occur and may also trigger podocytopathy as described in other cell types 68,69 .…”
Section: Discussionmentioning
confidence: 99%
“…Defects and mutations in the Wnt/β-catenin signaling pathway are usually related to human birth defects, cancer and other diseases (Logan and Nusse, 2004). Although endocrine disrupting chemical exposure during the early stages of fetal development has been linked to developmental delays and childhood cancers, to date only a few studies have reported their effects on the Wnt/β-catenin signaling pathway (Fang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant β-catenin expression is a key marker of Wnt-signaling activation and has been reported in male mouse reproductive cells by Fang et al (2015). In that study Fang et al (2015) evaluated the toxicological effects of prenatal to postnatal BPA exposure on the reproductive system of Institute of Cancer Research (ICR) male murine pups by evaluating the association between Wnt signaling and testis development. The expressions of β-catenin and DKK-1 were determined by immunohistochemical and western blot methods in the testicular tissues of the 6-week-old male mice.…”
Section: Effects Of Edcs On Wnt Pathwaymentioning
confidence: 99%
“…Increased β-catenin levels in this study indicate the inhibitory effect of BPA on β-catenin degradation (Kong and Zhang, 2009; Ye et al, 2011). On the other hand, the association of Wnt/β-catenin signaling pathway and BPA-induced inhibition of male mouse reproductive cell growth and development remains to be further elucidated (Fang et al, 2015).…”
Section: Effects Of Edcs On Wnt Pathwaymentioning
confidence: 99%